2007
DOI: 10.1144/0016-76492005-181
|View full text |Cite
|
Sign up to set email alerts
|

Structural contacts in subduction complexes and their tectonic significance: the Late Palaeozoic coastal accretionary wedge of central Chile

Abstract: Understanding the contact between the very low-grade metagreywacke of the Eastern Series and high-pressure metamorphosed schist of the Western Series in the Late Palaeozoic accretionary wedge of central Chile is fundamental for the understanding of the evolution of ancient accretionary wedges. We show the progressive development of structures and finite strain from the least deformed rocks in the eastern part of the Eastern Series of the accretionary wedge to high-pressure schist of the Western Series at the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 36 publications
3
89
0
11
Order By: Relevance
“…Along two prominent traverses from E to W, i.e., the Río Maule transect (Godoy, 1970;Richter et al, 2007) and along the abandoned railway line east of Pichilemu, it can be observed that a second foliation S 2 continuously evolves from a widely spaced foliation parallel to subhorizontal west-vergent open F 2 -folds ( Figs. 2A, B) with a penetrative transposition foliation S 2 that becomes increasingly fl attened towards the west, where it becomes the dominant regional foliation in the Western Series.…”
Section: The Eastern Seriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Along two prominent traverses from E to W, i.e., the Río Maule transect (Godoy, 1970;Richter et al, 2007) and along the abandoned railway line east of Pichilemu, it can be observed that a second foliation S 2 continuously evolves from a widely spaced foliation parallel to subhorizontal west-vergent open F 2 -folds ( Figs. 2A, B) with a penetrative transposition foliation S 2 that becomes increasingly fl attened towards the west, where it becomes the dominant regional foliation in the Western Series.…”
Section: The Eastern Seriesmentioning
confidence: 99%
“…For comparison of the results of both methods the conventional octahedral shear strain γ oct was determined. Both methods and their application are described in detail in Richter et al (2007). Along the Río Maule traverse in the southern part of the study area, these authors documented a continuous structural transition between the Eastern and Western Series caused by continuous variation of the strain parameters.…”
Section: Processes At the End Of Accretionmentioning
confidence: 99%
See 3 more Smart Citations